PPO.65 A legal and ethical debate on surrogate pregnany: successful challenge of the hfea defination motherhod. how will this affect doctors in the uk and eu countries?. (9th June 2014) - Burrell, C
Abstract : Background: In the UK there are no formal guidelines for Obstetricians, Commissioning Parents or Surrogates about pregnancy. There are no Obstetric or Paediatric Registry, audit or pregnancy follow-up. The "contract, " between the surrogate and commissioning couple is legally unenforceable. Method: Under UK jurisdiction, The Human Fertilisation and Embryology Act (HFEA) 2008 Section 33 dictates that the surrogate is the legal mother, irrespective of who donated the egg. This paper discusses a landmark case – (R and Another v An tArd Chlaraitheoir and Ors [2013] IEHC 91). Result: An Irish commissioning couple successfully challenged the HFEA 2008 legal definition of motherhood. - The Birth Registrar's legal representative argued that the medical records confirmed that the surrogate was the legal mother because she gave birth. - The commissioning couple's counsel proposed that the child was genetically from the commissioning couple highlighting the sacred mother-to-child blood link bond trumping other factors. - Irish High Court Judge's Verdict: Set a precedent by making the commissioning/genetic mother the legal mother; therefore allowed her to sign the children's birth certificate. Conclusion: Surrogacy is increasing because – (1) Advances in assisted reproductive technology, (2) Legislative changes - HFEA Act 2008 part 3 now gives same sex and unmarried couples equal rights as married couples in surrogacy arrangements. Learning points: (3) Although LEGALLY the commissioning couple can be regarded as the mother, doctors should have no conflict of interest because MEDICALLY the surrogate remains the mother and patient to whom a duty of care is owed.